Factors influencing the progress of mobilization in hip fracture patients during the early postsurgical period?—A prospective observational study. Issue 3 (May 2015) - Buecking, Benjamin; Bohl, Katharina; Eschbach, Daphne; Bliemel, Christopher; Aigner, Rene; Balzer-Geldsetzer, Monika; Dodel, Richard; Ruchholtz, Steffen; Debus, Florian
Highlights Cognitive ability was the most important factor for walking ability after surgery. Mobility after arthroplasty was superior compared to internal fixation at discharge. No factors were found that independently influence ability of standing.